Do ISO certifications enhance internationalization? The case of portuguese industrial SMEs - Pacheco, Luís Miguel (2022)
In the last decades, the academic literature has devoted considerable attention to the determinants of export performance. In result of those research efforts in identifying and examining the influence of such determinants, the literature presents a wide set of variables associated with higher levels of exports. This paper provides a contribution to that literature by trying to evidence the impact of firm certification—namely, in terms of the firm’s quality, environmental, and health and safety management systems—on export performance. The paper analyses an unbalanced sample of 1684 Portuguese industrial SMEs for the period 2010 to 2020, uses other determinants of internationalization as control variables, and explores the possibility of moderating effects on the certification–internationalization relationship. Two alternative econometric methods are employed: a random-effects model and a Tobit model. The results evidence the importance for firms, especially in the low or medium–low technology sectors, to have certain ISO certifications in order to further develop their export activities and increase their foreign acceptance, particularly in the European Union markets. Further, certification seems to reinforce the positive relation between firm size and internationalization.